STUDI TENTANG KECENDERUNGAN OBJEK RUMAH GADANG PADA KARYA LUKISAN NATURALIS KAMAL GUCI - ANITA GUSTINA, Ir. Drs. Heldi, M.Si, Drs. Efrizal, M.Pd (Serupa The Journal of Art Education, 2015)
This research aims (1) to describe the background of naturalist’s painting Kamal Guci which tend to visualize the object Rumah Gadang, (2) to describe the symbolic meaning of Kamal Guci’s painting which tend to visualize the object of Rumah Gadang, (3) to know the process of creating Kamal Guci’s painting which tend to visualize the object of Rumah Gadang. This research is using the qualitative methods with descriptive approach through snowball technique. The data sources of the research are paintings, written notes (recordings and photos) as the primary source, and the review of literature as secondary source. The procedure of collecting the data is conducted by doing observation, interview, and documentation. The research finding, that is, the background of Kamal Guci’s painting that tend to visualize the object of Rumah Gadang which is affected by anxiety and restlessness feeling to the culture and environment of Minangkabau. Generally, the meaning of Rumah Gadang on a painting is that to describe the changed that happens in Minangkabau as being identity of Minangkabau itself. The process of producing is exploration, improvisation, forming, and finishing.Kata kunci : Background of naturalist’s painting, symbolic meaning, process of creating.